Patient-reported vision impairment in low luminance relates to visual function in age-related macular degeneration: a MACUSTAR study report - Terheyden, Jan H.; Behning, Charlotte; Dunbar, Hannah M. P.; Poor, Stephen; Zakaria, Nadia; Binns, Alison M.; Saßmannshausen, Marlene; Leal, Sergio; Schmid, Matthias; Holz, Frank G.; Crabb, David P.; Luhmann, Ulrich F. O.; et al. (Scientific reports, 2025)
Early stages of age-related macular degeneration (AMD) can lead to a number of visual function deficits, but the patient relevance of these deficits is largely unknown. We therefore investigated how bilateral visual function domains affected by age-related macular degeneration (AMD) are associated with patient-reports. Using data from the cross-sectional part of the MACUSTAR study with 245 individuals with AMD (34 early AMD, 168 intermediate (i) AMD, 43 late AMD), the Vision Impairment in Low Luminance (VILL) questionnaire (subscales: reading, VILL_R; mobility, VILL_M; emotional well-being, VILL_E) and visual function assessments from both eyes (best-corrected and low-luminance visual acuity, BCVA, LLVA; Moorfields acuity, MA; contrast sensitivity, CS) were included. Associations between VILL and visual function data (better and worse eyes defined based on BCVA) were investigated using age- and sex-adjusted regression models. In the overall sample, VILL_R and VILL_M were associated with all functional tests across eyes (p ≤ 0.0389), while VILL_E was associated with MA and CS (p ≤ 0.0302). Regression estimates for BCVA, LLVA, MA and CS in the better-seeing eyes were -2.70, -1.84, -1.83 and 1.08 (VILL_R); -2.71, -1.87, -1.90 and 1.88 (VILL_M), and -0.25, -0.22, -2.15 and 1.57 (VILL_E). In iAMD, CS and MA in the worse-seeing eye were associated with two VILL subscales, respectively (VILL_R and VILL_M; VILL_M and VILL_E, respectively; p ≤ 0.0395), while BCVA and LLVA in the worse-seeing eye were both associated with one VILL subscale (VILL_M; p ≤ 0.0317). CS in the better eye was associated with VILL_M (p = 0.0454). Thus, patient-reported outcomes are associated with visual function assessments in both eyes in people with AMD. Contrast vision seems particularly patient-relevant in iAMD. Our results further support the construct validity of the VILL questionnaire.
Mitglieder des MACUSTAR consortium: H. Agostini, I.D. Aires, L. Altay, R. Atia [und viele weitere]
Gesehen am 08.01.2026